Rancang Bangun Blade Turbin Angin Jenis Taper Untuk Pembangkit Listrik Tenaga Bayu Berskala Mikro - Kusmayanto, La Ode Andi; Balaka, Ridway; Imran, Al Ichlas (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2021)
The ultization of renewable energy in Indonesian kept on doing as the increase of amount in energy electricity demand as well as environmentally friendly energy requerements, efficient and sustainable. This study aims to learn about the blade’s geometric shapes designed and crafted, as well as the blade’s performance. The study has bee succesfully designed and crafted as soon as tested by the blade’s for a low-scale wind turbine. The design blade’s geometry is a type of taper, is the Horizontal of Axis Wind Turbine type with airfoil NACA 6412. The blade was design with Qblade software and built with a manual engine. The method of data collection was the blade installed on the tower at 30 meters for three days. The energy generated on a daily basis that is the first day, the energy average production is 45,80 watts with an average wind speed of 4,54 m/s, the second day of 55,11 watts with and average wind speed of 5,23 m/s, and the third day of 72,27 watts with an average wind speed 5,14 m/s.Keywords:Airfoil, blade, energy, wind turbine